THE BEST METHODS OF MOTIVATION OF STUDENTS IN THE SPECIAL EDUCATION ENVIRONMENTS (Academia Science Repository, 2023)
This research paper is focusing on the main working methods of inspiration of student in the special educative atmosphere is scant in spite of some developments in education. This research made use of some basic online sites to comprehend what is motivation and why it is highly needed in special education sphere. This question is important as for every student's development motivation plays an exponential and essential role. The aim of this research is to identify as many ways of how to inspire students in special environments as possible. Responses indicated that three major routes for having great motivation are higher potential, productive career path and exponential growth for working field. So, in this paper I will highlight the importance of motivation of learners in special education sphere. During the research it was found out that mostly female suffer from lack of encouragement compared to male. The most functional site of identification for my questionnaire is unbelievably the percentages of attendants.